Changes in Gene Expression in Leaves of Cacao Genotypes Resistant and Susceptible to Phytophthora palmivora Infection - Baruah, Indrani K.; Ali, Shahin S.; Shao, Jonathan; Lary, David; Bailey, Bryan A. (Frontiers in Plant Science, 2022)
Black pod rot, caused by Phytophthora palmivora, is a devastating disease of Theobroma cacao L. (cacao) leading to huge losses for farmers and limiting chocolate industry supplies. To understand resistance responses of cacao leaves to P. palmivora, Stage 2 leaves of genotypes Imperial College Selection 1 (ICS1), Colección Castro Naranjal 51 (CCN51), and Pound7 were inoculated with zoospores and monitored for symptoms up to 48 h. Pound7 consistently showed less necrosis than ICS1 and CCN51 48 h after inoculation. RNA-Seq was carried out on samples 24 h post inoculation. A total of 24,672 expressed cacao genes were identified, and 2,521 transcripts showed induction in at least one P. palmivora-treated genotype compared to controls. There were 115 genes induced in the P. palmivora-treated samples in all three genotypes. Many of the differentially expressed genes were components of KEGG pathways important in plant defense signal perception (the plant MAPK signaling pathway, plant hormone signal transduction, and plant pathogen interactions), and plant defense metabolite biosynthesis (phenylpropanoid biosynthesis, α-linolenic acid metabolism, ethylene biosynthesis, and terpenoid backbone biosynthesis). A search of putative cacao resistance genes within the cacao transcriptome identified 89 genes with prominent leucine-rich repeat (LRR) domains, 170 protein kinases encoding genes, 210 genes with prominent NB-ARC domains, 305 lectin-related genes, and 97 cysteine-rich RK genes. We further analyzed the cacao leaf transcriptome in detail focusing on gene families-encoding proteins important in signal transduction (MAP kinases and transcription factors) and direct plant defense (Germin-like, ubiquitin-associated, lectin-related, pathogenesis-related, glutathione-S-transferases, and proteases). There was a massive reprogramming of defense gene processes in susceptible cacao leaf tissue after infection, which was restricted in the resistant genotype Pound7. Most genes induced in Pound7 were induced in ICS1/CCN51. The level of induction was not always proportional to the infection level, raising the possibility that genes are responding to infection more strongly in Pound7. There were also defense-associated genes constitutively differentially expressed at higher levels in specific genotypes, possibly providing a prepositioned defense. Many of the defense genes occur in blocks where members are constitutively expressed at different levels, and some members are induced by Ppal infection. With further study, the identified candidate genes and gene blocks may be useful as markers for breeding disease-resistant cacao genotypes against P. palmivora.